A comparison of fuzzy time series and ARIMA to forecast tourist arrivals to homestay in Pahang / Maizatul Akhmar Jafridin ... [et al.] - Jafridin, Maizatul Akhmar; Fauzi, Nur Fatihah; Alias, Rohana; Ab Halim, Huda Zuhrah; Ahmad Bakhtiar, Nurizatul Syarfinas; Khairudin, Nur Izzati; Shafii, Nor Hayati (UiTM Cawangan Perlis, 2021)
Predictions of future events must be incorporated into the decision-making process. For tourism demand, forecasting is very important to help directors and investors to make decisions in operational, tactical, and strategic decisions. This study focuses on forecasting performance between Fuzzy Time Series and ARIMA to forecast the tourist arrivals in homestays in Pahang. The main objective of this study is to compare and identify the best method between Fuzzy Time Series and Autoregressive Integrated Moving Average (ARIMA) in forecasting the arrival of tourists based on the secondary data of tourist arrivals to homestay in Pahang from January 2015 to December 2018. ARIMA models are flexible and widely used in time-series analysis and Fuzzy Time Series which do not need large samples and long past time series. These two methods have been compared by using the mean square error (MSE) and mean absolute percentage error (MAPE) as the forecast measures of accuracy. The results show that Fuzzy Time Series outperforms the ARIMA. The lowest value of MSE and MAPE was obtained from using the Fuzzy Time Series method at values 2192305.89 and 11.92256, respectively.